2010
DOI: 10.1080/14786430902998129
|View full text |Cite
|
Sign up to set email alerts
|

Grain growth in thin films with a fibre texture studied by phase-field simulations and mean field modelling

Abstract: The Harvard community has made this article openly available. Please share how this access benefits you. Your story matters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 53 publications
1
21
0
2
Order By: Relevance
“…Only at junctions where three or more grain boundaries intersect, a finite contribution is neglected by omitting the dependence of . The results in Table I and other applications of the model 37,63 show that the theoretical equilibrium angles at triple junctions are well reproduced, if the resolution of the numerical technique is high enough. Nevertheless, it remains to be analyzed in more detail if and to which extent restrictions ͑56a͒-͑56c͒ affect, for example, the kinetic behavior of multijunctions in the simulations.…”
Section: E Difficulties Of a Fully Variational Approach With Respectmentioning
confidence: 52%
“…Only at junctions where three or more grain boundaries intersect, a finite contribution is neglected by omitting the dependence of . The results in Table I and other applications of the model 37,63 show that the theoretical equilibrium angles at triple junctions are well reproduced, if the resolution of the numerical technique is high enough. Nevertheless, it remains to be analyzed in more detail if and to which extent restrictions ͑56a͒-͑56c͒ affect, for example, the kinetic behavior of multijunctions in the simulations.…”
Section: E Difficulties Of a Fully Variational Approach With Respectmentioning
confidence: 52%
“…The paper [1] modified and combined the two kinetic modeling frameworks from [14,22] as applied to the particular case of polycrystalline thin films with so-called fiber textures. In this sufficiently narrow case, grains have nearly identical orientations in the axial direction perpendicular to a considered film, but random radial orientations in the plane of the film; see also [18]. In comparison with [14], the dependence of the kinetic model on large-scale simulations was essentially decreased.…”
Section: Introductionmentioning
confidence: 96%
“…In this situation, the further reduction in the interface energy can be reached only by decreasing the total measure of grain boundaries; see, for instance, [8,9]. Important statistical descriptors of grain boundary networks are misorientation distribution functions (often referred to as grain boundary character distributions), which show relative measures of interfaces with given misorientation parameters; see [1,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In order to investigate how the structure and time evolution of misorientation distribution functions depend on the grain boundary energy anisotropy and set of laws governing the dynamics at a microscopic scale, it is possible to conduct numerical experiments via well-known large-scale simulation approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase field model, on the other hand, is able to handle the complex geometry of microstructures since interfaces are diffuse and their motion can be characterized without explicit kinetic laws. Because of this advantage, the phase field method has been widely applied to model the grain growth in bulk materials [12][13][14][15][16][17][18][19][20][21][22][23][24]. It was shown that the phase field model is capable of revealing various characteristics of grain growth such as the evolution of average grain size and grain size distribution.…”
mentioning
confidence: 99%